2019
DOI: 10.1080/24725838.2019.1638331
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exoskeletons: Overview of Their Benefits and Limitations in Preventing Work-Related Musculoskeletal Disorders

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 62 publications
2
77
1
4
Order By: Relevance
“…The primary consequence of muscle activity reduction is the de-compression of the lumbar spine. Such results are confirmed by a more recent review (Theurel and Desbrosses, 2019 ) that stresses the clear potential of exoskeletons in limiting muscular demand. However, this report also warns that there is insufficient current knowledge to justify an unreserved adoption of this technology.…”
Section: Introductionsupporting
confidence: 72%
“…The primary consequence of muscle activity reduction is the de-compression of the lumbar spine. Such results are confirmed by a more recent review (Theurel and Desbrosses, 2019 ) that stresses the clear potential of exoskeletons in limiting muscular demand. However, this report also warns that there is insufficient current knowledge to justify an unreserved adoption of this technology.…”
Section: Introductionsupporting
confidence: 72%
“…The fact that the tests were conducted with a group of healthy young subjects in two specific overhead work activities can be seen as a general limitation of the study. Further studies should be conducted to address the question whether these results can be generalized to subjects of older age groups and for other overhead activities [14,15]. Furthermore, previous studies demonstrated that decreased loads in one part of the body may result in increased strain to other areas due to weight transfer by the exoskeleton and its own weight [27,31].…”
Section: Discussionmentioning
confidence: 99%
“…This rarely used method indicates the metabolic effort a worker has to put into the execution of such activity [12,13]. Despite positive reports describing the benefits exoskeletons offer during overhead work, evidence regarding their functionality as well as possible adverse effects have become the subject to scientific discussion [14,15,16,17]. For example, it is important that the load transfer and possible kinematic changes do not significantly increase strain to other parts of the body, e.g., the lower back or pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies generally agree on the efficiency of passive back-support exoskeletons to reduce lumbar muscular activity and perceived exertion/discomfort, particularly during operations involving trunk flexion/extension in the sagittal plane [9,10]. However, although occupational exoskeletons are deployed in the industrial sector [11], their use in the healthcare system is rarely reported, with no reported use in ICUs.…”
Section: Letter To the Editormentioning
confidence: 93%